Marzouki, Abou Yareb. “Existential Evidence (Al-Dalīl al-Wujūdī al-Ḥulūlī) or Conditions of Breaking Away from Germanic Neoplatonism,” Year 3, Issue 11 (Winter 1418 AH/ 1998 CE), Pp. 9-48. - المرزوقي أبويعرب (Al-Fikr al-islāmī al-muʿāṣir (previously Islamiyat al-Ma’rifah), 1998)
Abou Yareb Marzouki’s article criticizes the existential reincarnation evidence (al-dalīl al-wujūdī al-ḥulūlī ) in its incarnation-based structure in Western philosophical thought, discussing the views of Kant, Hegel, Schelling, Descartes, Schopenhauer, and others, and discovers the existence of these views in the Islamic kalām (theology) and philosophical thought of Ibn Sīnā, al-Ghazālī, and Ibn Rushd. It describes the misrepresentation and distortion that befell those original thoughts in the context of Germanic Neoplatonism, and criticizes historians of Western thought for their neglect, intentionally or inadvertently, of their predecessors of Muslim thinkers and philosophers. It explains the essential foundations on which the theory of value, and the foundations of Kant’s refutation of existential evidence are based. And it discusses the theory of acts and Kant’s statements on it, and the existential incarnation-based evidence between Descartes and Schelling.